Chapter: ''Rapt Up with Joy': Children's Emotional Responses to Death in Early Modern England' from book: Death, Emotion and Childhood in Premodern Europe - Hannah Newton (Palgrave Studies in the History of Childhood, 2017)
Valuable scholarship has been produced on parents' responses to the deaths of children in early modern England, but the emotional experiences of the young themselves have rarely been explored. This chapter seeks to rectify this deficiency by viewing death through the child's eyes. Taking advantage of recent insights from the history of emotions, Newton argues that dying children expressed diverse and conflicting passions, from fear to ecstasy. The underlying question is to what extent children's experiences differed from those of adults. While the range of emotions was similar, the preoccupations of children differed; these included a concern about surviving siblings, and a more vivid imagination of heaven. Through highlighting such distinctions, we come closer to what it was like to be an early modern child.